Hepatic mitochondrial adaptations to physical activity: impact of sexual dimorphism, PGC1α and BNIP3‐mediated mitophagy. (28th August 2018) - Von Schulze, Alex; McCoin, Colin S.; Onyekere, Chiemela; Allen, Julie; Geiger, Paige; Dorn, Gerald W.; Morris, E. Matthew; Thyfault, John P.
Abstract : Key points: Hepatic mitochondrial adaptations to physical activity may be regulated by mitochondrial biogenesis (PGC1α) and mitophagy (BNIP3). Additionally, these adaptations may be sex‐dependent. Chronic increase in physical activity lowers basal mitochondrial respiratory capacity in mice. Female mice have higher hepatic electron transport system protein content, elevated respiratory capacity, lowered mitophagic flux, and emit less mitochondrial H2 O2 independent of physical activity. Males require chronic daily physical activity to attain a similar mitochondrial phenotype compared to females. In contrast, females have limited hepatic adaptations to chronic physical activity. Livers deficient in PGC1α and BNIP3 display similar mitochondrial adaptations to physical activity to those found in wild‐type mice. Abstract: Hepatic mitochondrial adaptations to physical activity may be regulated by biogenesis‐ and mitophagy‐associated pathways in a sex‐dependent manner. Here, we tested if mice with targeted deficiencies in liver‐specific peroxisome proliferator‐activated receptor γ coactivator 1α (PGC1α; LPGC1α +/− ) and BCL2/adenovirus E1B 19 kDa protein‐interacting protein 3 (BNIP3)‐mediated mitophagy (BNIP3 −/− ) would have reduced physical activity‐induced adaptations in respiratory capacity, H2 O2 emission and mitophagy compared to wild‐type (WT) controls and if these effects were impacted by sex. Male and female WT, LPGC1α +/− and BNIP3 −/− C57BL6/J mice were divided into groups that remained sedentary or had access to daily physical activity via voluntary wheel running (VWR) ( n = 6–10/group) for 4 weeks. Mice had ad libitum access to low‐fat diet and water. VWR reduced basal mitochondrial respiration, increased mitochondrial coupling and altered ubiquitin‐mediated mitophagy in a sex‐specific manner in WT mice. Female mice of all genotypes displayed higher electron transport system content, displayed increased ADP‐stimulated respiration, produced less mitochondrially derived reactive oxygen species, exhibited reduced mitophagic flux, and were less responsive to VWR compared to males. Males responded more robustly to VWR‐induced changes in hepatic mitochondrial function resulting in a match to adaptations found in females. Deficiencies in PGC1α and BNIP3 alone did not largely alter mitochondrial adaptations to VWR. However, VWR restored sex‐dependent abnormalities in mitophagic flux in LPGC1α +/− . Finally, BNIP3 −/− mice had elevated mitochondrial content and increased mitochondrial respiration putatively through repressed mitophagic flux. In conclusion, hepatic mitochondrial adaptations to physical activity are more dependent on sex than PGC1α and BNIP3. Key points: Hepatic mitochondrial adaptations to physical activity may be regulated by mitochondrial biogenesis (PGC1α) and mitophagy (BNIP3). Additionally, these adaptations may be sex‐dependent. Chronic increase in physical activity lowers basal mitochondrial respiratory capacity in mice. Female mice have higher hepatic electron transport system protein content, elevated respiratory capacity, lowered mitophagic flux, and emit less mitochondrial H2 O2 independent of physical activity. Males require chronic daily physical activity to attain a similar mitochondrial phenotype compared to females. In contrast, females have limited hepatic adaptations to chronic physical activity. Livers deficient in PGC1α and BNIP3 display similar mitochondrial adaptations to physical activity to those found in wild‐type mice.